Hybrid Analysis of Marriage Information System Using Webqual 4.0, EUCS, and Importance-Performance Matrix Method - Muhamad Fauzi; Umi Laili Yuhana (IPTEK The Journal for Technology and Science, 2022)
Electronic-based governance is a way for Central and Regional Government Agencies to utilize information technology. Ministry of religion created SIMKAH WEB as one of the forms of E-government. This application helps administer marriages and is integrated with other applications by sector. The primary purpose of this application is to improve services and digital data presentation. This study analyzes the quality of SIMKAH WEB based on user perceptions, namely employees of the Ministry of Religion and prospective brides. The method used in this research is Webqual 4.0, EUCS, and Importance Performance Analysis Matrix. We combined the two approaches, Webqual and EUCS, and then analyzed them with the IPA Matrix. The result was compared against the results given by each method when it was carried out separately. Another benefit is providing recommendations for improvement based on each technique. Several methods will show which way has the highest suitability level and provide suggestions for improving the SIMKAH application. Based on the suitability level analysis results, the combined Method obtained a value of 92.85%, EUCS 92.64%, and Webqual 90.13%